Implementation of the Building Permit Policy in terms of Communication and Resources Aspects in Palu City - Nuraisyah, Nuraisyah; Natsir, Syahir; Mangngasing, Nasir; Daswati, Daswati (International Journal Papier Public Review, 2020)
This study aims to analyze the implementation of the Building Permit Policy in Palu City. This study looks specifically at the aspects of communication and resources. This type of sub-district is descriptive qualitative. The sub-district location determined by the sub-districter is Palu City. The informants are 9 people, namely those who understand, know, experience and understand what will be sub-districted, especially related to the policy of building permits in Palu City, such as the Palu City Spatial Planning and Land Office by extracting information through observations and interviews. The results showed that one of the reasons was due to the lack of socialization by the Palu City Spatial Planning and Land Planning (DPRP) officials. In fact, communication is crucial to success in implementing policies effectively. Human resources in terms of quality are adequate but in terms of quantity they are inadequate and facilities and infrastructure that can be used as operational tools are inadequate.